The problem of multiple commons: A market design approach - Ryan Tierney (Osaka University, Institute of Social and Economic Research (ISER), 2016)
There are several locations, each of which is endowed with a resource that is specific to that location. Examples include coastal fisheries, oil fields, etc. Each agent will go to a single location and harvest some of the resource there. Several agents may go to each location. We assign harvesting rights based on preferences alone, though we later extend the model to accommodate private endowments of money. We find the best allocation rule in the class of rules that are strategy-proof, anonymous, and that satisfy a weak continuity property. We also find an ascending mechanism, similar to an auction, that implements the rule. The rule coincides with a special simulated price equilibrium, wherein agents buy their desired resource with tokens distributed by the social planner. Equilibrium price vectors form a lower semi-lattice and thus there is a unique minimal price vector. The equilibria associated with the minimal price vector are called min-price Walrasian equilibria. These equilibria form an essentially single-valued correspondence, and this correspondence is the rule we characterize.
Keywords: 330; Incentive-compatibility; min-price equilibrium; commons; indivisible goods